On Pragmatic Competence: Politeness Strategies used by Acehnese Students - Fera Busfina Zalha (Bansigom Na Publisher, 2026)
Pragmatic competence is a fundamental element in social interaction that allows speakers to adapt their messages to specific social and cultural contexts. This study aims to analyze the politeness strategies employed by Acehnese students in academic and social environments and to identify the sociolinguistic factors influencing these strategic choices. Utilizing Brown and Levinson's politeness theory and Leech’s politeness principles, this research explores how the concept of